Dentition Anomalies and Cranial Abnormalities in Invasive Beavers (Castor canadensis) in Tierra Del Fuego, Argentina - Alvaro González-Calderón (Animals, 2024)
The study of dentition anomalies and pathologies in wildlife contributes, together with other indicators, to understanding the relevance of some factors on the health status of populations. This has not been properly evaluated in invasive mammals. To test the feasibility of eradication, the government of Tierra del Fuego performed the eradication of beavers (Castor canadensis) from 2016 to 2018: 1121 animals were removed and 970 examined. These beavers were examined to analyze the incidence of dentition anomalies and other dentition and cranial conditions. The beavers presented two dentition anomalies: hypodontia and hyperdontia (0.41% in both cases), and for the first time, a dentition anomaly in the upper quadrants was reported. Beavers also presented artifactual tooth loss (0.30%) and acquired tooth loss (0.61%) but with low incidence. The presence of fractured teeth (0.41%) and caries (0.31%) occurred in all age classes, also with low incidence. The third molar tooth was the most affected, showing a female bias. The 0.93% of skulls had a cranial abnormality represented as a buccal curvature. Malocclusion cases also were recorded (0.51%). The low prevalence of dentition anomalies, fractured teeth, caries, and cranial abnormalities would not compromise the lifespan of beavers. These results leave a precedent of dentition anomalies and dentition and cranial conditions in an invasive mammal.